Observations of tidal and storm surge attenuation in a large tidal marsh. (15th May 2015) - Stark, J.; Van Oyen, T.; Meire, P.; Temmerman, S.
Abstract Tidal wetlands are increasingly valued for their role in coastal defense. Nevertheless, in situ observations of storm surge attenuation within wetlands are still scarce. We present water level measurements along a 4 km intertidal channel and on the surrounding marsh platform for regular spring to neap tides and two major storm surge tides, showing the effects of flood wave height and marsh geomorphology on the amount of flood wave attenuation. Undermarsh tides with peak water levels below marsh platform elevation are mostly amplified (up to 4 cm/km) within the channels. Overmarsh tides with peak water levels above the marsh platform are generally attenuated along the channels, with maximum attenuation rates of 5 cm/km for tides that inundate the marsh platform by 0.5–1.0 m. For lower or higher flood waves, including storm surges, attenuation rates decrease. Furthermore, the observations show that the maximum attenuation occurs along narrow channel transects where the width of the platform is larger, whereas attenuation rates are lower along wider channels with smaller adjacent marsh platforms. These observations are confirmed by an analytical approximation of tidal wave propagation through convergent channels. The analytical model indicates that differences in attenuation rates are induced by variations in the cross‐channel averaged friction between channel sections and between tides with varying peak water levels. Finally, the highest attenuation rates of up to 70 cm/km are observed over short distances on the vegetated marsh platform. We conclude that this study provides an empirical basis for the wider implementation of nature‐based flood defense strategies.